Iwokrama: the Commonwealth Rain Forest Programme in Guyana (Commonwealth Secretariat LondonGB)
Gives a brief summary of the programme. Includes aspects such as the origin of the programme; amenindians in relation to the programme; the Swaminathan Report, 1990; financial aspects; the Phase I survey; remote sensing of site surveys; and scientific organisations in Guyana.
DC